ISLAMIC PROPAGATION MOVEMENT ON NATIONALIST PARADIGM - Abdul Hamid (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Abstract: The Indonesian nation is independent and was formed by the contribution of scholars who preached with a high sense of nationalism. As the largest Muslim country, Indonesia has an important role in the Islamic world, so that its position is taken into account. Both have an important role and support each other. This article is a literature review that discusses the Islamic propagation movement nationalist paradigm using a qualitative approach and literature study methods. The Islamic propagation (da’wah) paradigm defined in this article is the fundamental view, framework and rationale used in preaching. Based on the movements carried out by the perpetrators, the paradigm is classified into three, namely the tabligh paradigm, the community development paradigm, the harakah paradigm and the cultural paradigm. One part of da'wah with a cultural paradigm, namely national da'wah. National da'wah in Indonesia has the following characteristics: 1) National da'wah must accommodate differences in backgrounds; 2) National da'wah must be based on the pillars of nationality, and 3) National da'wah upholds the universal and eternal values of Islamic teachings.